Effect of tillage practices and genotypes on growth, seed yield and nutrient uptake in wheat (Triticum aestivum) - RAM, H; SINGH, R K; PAL, G; AGARWAL, D K; KUMAR, R (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted to evaluate the effect of tillage practices on growth, seed yield and nutrient uptake of promising wheat (Triticum aestivum L.) genotypes during winter seasons of 2012-13 to 2014-15 at the research farm of the Indian Institute of Seed Science, Mau, India. Based on mean data over three years we observed that contrasting tillage practices, zero tillage (ZT) treatment recorded significantly higher LAI, CGR, RGR, NAR and no. of effective tillers/m2 over conventional tillage (CT) and raised beds (RB). However, significantly higher no. of seeds/spike and test weight was recorded in RB followed by ZT and lowest in CT. Significant effect of tillage practices was also recorded for seed yield and nutrient uptake. Significantly higher seed yield was recorded under ZT (47.9 q/ha) and CT (45.3 q/ha) as compared to RB (33.0 q/ha). The maximum mean net return was obtained under ZT (Rupees 78.1 × 103/ha) followed by CT (Rupees 65.6 × 103/ha) and least in RB (Rupees 43.9 × 103/ha). The total nutrient (NPK) uptake was significantly higher under ZT followed by CT and least in RB. Genotype variations were also found in respect to growth parameters, seed yield and nutrient uptake. Genotype, HD 2967 performed significantly better in all growth parameters, viz. LAI, CGR, RGR and NAR over KRL 213, HD 2733, PBW 550, PBW 502 and DBW 39. The no. of effective tillers/m2, seeds/spike and test weight were also significantly superior over other genotypes. Among genotypes, HD 2967 proved as paramount in realizing the highest seed yield (46.54 q/ha), net returns (Rupees 70.5 × 103/ha), B: C ratio (2.57) and nutrient uptake (NPK) indicating their better adaptability and yield advantage over other genotypes.